Factors in cognitive processing of Japanese loanwords by advanced Chinese Japanese-as-a-foreign-language learners - Geng, Yaoyao; Song, Qichao; Fei, Xiaodong (Frontiers in Psychology, 2023)
Previous studies have highlighted the challenges faced by Chinese Japanese-as-a-foreign-language (JFL) learners (whose L2 is English) in acquiring L3 Japanese loanwords. However, there is a lack of research on the specific factors that impact the processing of Japanese loanwords among Chinese JFL learners. This study investigates the impact of four such factors, English-Japanese phonological similarity, loanword familiarity, context, and English vocabulary proficiency, on the processing of Japanese loanwords. Data analysis, using a (generalized) linear mixed-effect model, shows that among the four factors examined, loanword familiarity has the most significant impact, and that the impact from context and phonological similarity on the processing of Japanese loanwords are not consistently positive. As Chinese JFL learners improve their proficiency in L3 Japanese, they tend to decrease their reliance on English knowledge and instead access loanword representations directly to conceptual representations. Finally, based on the findings of this study, a processing model for Japanese loanwords among advanced Chinese JFL learners is proposed.